(untitled) (Altre Modernità, 2023)
Our Home by the Adriatic (1886) by Margaret Collier is a travel book which provides historical, social and cultural knowledge about the people, spaces and places of the Italian region of the Marche. Collier’s marriage to a former Garibaldian officer was the occasion for her move to Italy, where her need to write developed as something different from that of a tourist. Indeed, her topographical writing was spurred by her desire to prove that women were capable of traveling and writing (Mangani), and to undermine the stereotype of the woman who “[…] could not write so well; [if she did] it was her brother’s, no doubt” (Battestin 380-381). Beyond the gender dimension, the essay will survey how Collier’s travel writing depicts through its anthropological approach both the lights and the shadows of the Marche, and how the portrayal of the region itself proves to be crucial to her understanding of place and perception of space.